2020
DOI: 10.2196/24012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Deteriorating Depression and Anxiety With Longitudinal Behavioral Changes in Google and YouTube Use During COVID-19: Observational Study

Abstract: Background Depression and anxiety disorders among the global population have worsened during the COVID-19 pandemic. Yet, current methods for screening these two issues rely on in-person interviews, which can be expensive, time-consuming, and blocked by social stigma and quarantines. Meanwhile, how individuals engage with online platforms such as Google Search and YouTube has undergone drastic shifts due to COVID-19 and subsequent lockdowns. Such ubiquitous daily behaviors on online platforms have t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 65 publications
2
78
0
Order By: Relevance
“…The literature has approved that the COVID-19 pandemic has caused serious mental, physical and emotional problems among hospital staff who are at a higher risk of contracting the infection or even passing on the disease to others. [27][28][29] The other cause of anxiety among HCWs might be working in high-infectious work environments with inadequate access to PPE. 30 A number of systematic reviews and meta-analyses have reported the prevalence of anxiety among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has approved that the COVID-19 pandemic has caused serious mental, physical and emotional problems among hospital staff who are at a higher risk of contracting the infection or even passing on the disease to others. [27][28][29] The other cause of anxiety among HCWs might be working in high-infectious work environments with inadequate access to PPE. 30 A number of systematic reviews and meta-analyses have reported the prevalence of anxiety among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the screening process, 19 articles were included in the systematic review. 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52
Fig. 1 Flow diagram of the study-selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains unclear whether spikes in posts with negative affect detected during and following disasters are clinically meaningful changes warranting intervention or the natural course of psychopathology following a distressing event (Galea & Norris, 2006). More participatory research could address this issue by combining passive SNS monitoring with validated psychological measures capable of capturing both distress and dysfunction in the affected population (e.g., Zhang et al, 2020). Further, little research has examined the use of SNS to assess the impact of disasters on the mental health of vulnerable populations, including those with pre-existing mental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Next, two studies used mental health forum membership to indicate mental health problems (Low et al, 2020;Saha & De Choudhury, 2017), with Saha and De Choudhury (2017) using the novel method of transfer learning from a classifier trained on a mental health subreddit (r/stress) and a random sample of Reddit posts to identify posts with high stress on college-specific subreddits following gun-related violence on campus. Finally, mental health questionnaires were used in two studies; specifically, the PHQ-9 and GAD-7 in Zhang et al (2020) and PWB Scale in Wang et al (2020).…”
Section: Disaster Mental Health Methodsmentioning
confidence: 99%
See 1 more Smart Citation